Factor pricing and economic growth in underdeveloped rural areas - Bottomley, Anthony (London : Crosby Lockwood, 1971)
This book forms an attempt to fit existing factor pricing analysis to conditions prevailing in underdeveloped rural areas. The book is divided into four sections. Section one deals with wage rates, labour supply and output in underdeveloped areas. Section two and three deals with rent determination and interest rates, cost and availability of loans and credit comparison respectively. the final section on profits discusses the determination of gross rural income and rural factor cost.
Includes index
Includes bibliographical references.
usc 25/01/2019
Loans
Keywords: Factor analysis; Economic development; Developing countries